Survey on Methods of Obtaining Biomedical Parameters from PPG Signal (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In today’s world effective monitoring of biomedical parameters are essential. There are several applications that use these parameters to analyze the health conditions of an individual. PPG signal is one of the vital biomedical parameters which can be obtained by non-invasive method. Extracting necessary details from this signal is a crucial task. PPG signal contains various information such as rate at which heart beats, respiration rate, blood pressure, etc. Effective methods required to get necessary details from a raw PPG signal. Let us study various algorithms that are used to extract these features, along with its pros and cons.